Impact of Incorporating White Oyster Mushrooms (Pleurotus ostreatus) in Chicken Meatball Formulation on Moisture Content and Sensory Properties - Irsalina Dwi Meiliany (Universitas Veteran Bangun Nusantara, 2024)
Avenue for reducing meat consumption in chicken meatballs. This research aimed to assess the impact of incorporating oyster mushrooms on both the moisture content and sensory properties of meatballs. The study involved four treatment groups, each with varying proportions of chicken meat and oyster mushrooms: P1 (100% chicken meat: 0% oyster mushrooms), P2 (90% chicken meat: 10% oyster mushrooms), P3 (80% chicken meat: 20% oyster mushrooms), and P4 (70% chicken meat: 30% oyster mushrooms). Notably, the research findings demonstrated that the addition of oyster mushrooms significantly influenced moisture content and organoleptic characteristics. The resulting moisture content met quality standards for combined meatballs. Furthermore, sensory testing revealed that meatball formulation P1 (100% chicken meat: 0% oyster mushrooms) yielded the highest sensory value compared to formulations with 10%, 20%, and 30% oyster mushroom additions.